Potential of Endophytic Bacteria from Pauh Stems (Mangifera sumatrana Miq) as Antimicrobials - Zaunit, Muthia Miranda; Verawati, Verawati; Anela Putri, Suci; Fera, Okta (Program Studi Farmasi, 2023)
Background: Endophytic bacteria are microorganisms whose life cycle resides in plant tissue without causing damage to the host and are capable of producing bioactive compounds, one of which is antibacterial compounds from the papuh plant (Mangifera sumatrana Miq.). Objective: This study aims to isolate and test the antimicrobial activity of endophytic bacteria in the stems against Staphylococcus aureus, Escherichia coli and Candida albicans and to carry out molecular identification using the 16S rRNA gene against endophytic bacteria that have the greatest antimicrobial power. Method: Antimicrobial activity testing was carried out using the disc diffusion method. Results: The results of the characteristics of endophytic bacteria obtained using the planting method were 6 isolates, namely 4 isolates from the outer stem (BL1, BL2, BL3, and BL4) and 2 isolates from the inner stem (BD1 and BD2). The results of the antimicrobial activity test for isolates BL2 and BL3 against Staphylococcus aureus found an inhibition zone of 13.20 mm and 12.05 mm, whereas against Candida albicans and Escherichia coli, they had no antimicrobial activity. The results of molecular identification show that the BL2 is Bacillus altitudinis. Conclusions and suggestions: Bacterial isolates from pauh stems have the potential to be antibacterial.